The millennium and beyond the prophecies, your potential - Moorey, Teresa (Hodder & Stoughton, 1999)
This guide discusses all the prophecies about the new century and looks forward to a new future. It looks at astrological predictions, the codes of the pyramids and the Bible, Nostradamus, the Hopi and Mayan, UFOs, lost continents and new technology.